Review. An overview on the environmental behaviour of pesticide residues in soils - Navarro, S.; Vela, N.; Navarro, G. (Spanish Journal of Agricultural Research, 2007)
The current state of knowledge of the main aspects regarding the behaviour and fate of pesticide residues in the soil environment is reviewed in this article. Once a pesticide is introduced into the environment, whether by application, disposal, or a spill, it can be influenced by many processes. Physical and chemical properties of the pesticide, site characteristics, such as soil, geology, and vegetation, environmental conditions, crop management systems, and chemical handling practices can all affect each process. Each factor must be considered when determining the likelihood of pesticide movement and off-target effect. These fate processes can have both positive (they can bring a pesticide in contact with the target pest) and negative (leading to injury of nontarget plants and animals) influences on a pesticide’s effectiveness or its impact on the environment. Processes responsible for accumulation, movement and disappearance of pesticides in the soil and the factors involved in their dynamics are assessed. Also, the environmental significance of the formation of bound residues and some techniques used currently for remediation of pesticide-contaminated soils are discussed according to the recent researches